Ovarian and uterine disturbances occured in the puerperium of cows and their relationship with progesterone in the milk - Kozicki, Luiz Ernandes; Bostedt, Heinrich; Finger, Karl I.; Arnstadt, Ingo (Pesquisa Agropecuaria Brasileira, 2014)
Seventy-two dairy cows were submitted to weekly rectal palpation exames until 42nd day post-parturition (p.p.) and progesterone dosages by Radioimmunoassay (RIA) and Enzymimmunoassay (EIA) until the 72nd day p.p., were performed. It was observed that 9.7% of the animals bore follicular cysts, 6.9% were completely acyclic, 6.9% had corpus luteum persistens or luteinic cyst, 22.2% were affected by endometritis and 6.9% had endometritis associated with follicular cysts. Follicular cysts appeared in average on the 29 ± 8.1 day p.p. while the first progesterone peak occurred on the 56.4 ± 7.8 day p.p. Cases of luteinic cysts or corpus luteum persistens appeared only after the 42nd day p.p. Inadequate obstetric manipulations at parturition time could rise very much the endometritis incidence in a given herd.